SE DIO TE LASCI, LETTOR. ASPECTOS DA AUTOTEORIZAÇÃO EM FANNY OWEN, DE AGUSTINA BESSA-LUÍS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The subject of this study is the self-theorization in the novel Fanny Owen (1979) by Portuguese writer Agustina Bessa-Luís. The self-theorization occurs when literature looks at itself in a movement of self-reflexivity. Fanny Owen herself is entirely a self-theorization exercise. Her work is a fictional treatment of biographical facts related to historical personalities – mainly to the writer Camilo Castelo Branco, to his friend José Augusto Pinto de Magalhães, and to Fanny Owen, daughter of the British Colonel Hugh Owen , who had a leading role in the Portuguese Civil War (1828 -1834) . These three characters are involved in a love triangle. The narrative presents as a background the cultural context dominated by the Romantic movement, which has notable influence on the characters, especially on Fanny and Jose Augusto, readers of literature – mainly of Lord Byron. Given the importance that the theme of the literature appears in Fanny Owen, it seemed appropriate to allocate it in the subgenre "novel of reading", concept created by German theorist Volker Rollof. The novel of reading is that work whose reading of literature by its characters featured prominently in the plot. Such a condition of the work herein studied favors our approach of the self-theorization theme, since this category of novels, when addressing the relationship between reader and literature reading, necessarily establishes a discussion on the literary phenomenon. However, self-theorization also appears at other levels in this novel. It occurs through the narrator, who at several moments uses strategies in an attempt to be confused with the empirical author and that, moreover, mind-wanders about the art of writing. It also occurs when it portrays the writer Camilo Castelo Branco as a writer in training. Chapter I addresses specifically the self-theorization theme and reflections supported by theoretical contributions from Jonathan Culler, Antoine Compagnon, David Lodge, Umberto Eco, Lelia Pereira Duarte and Karin Volobuef. In Chapter II, it begins the study of the novel Fanny Owen discussing its main themes: the romantic culture, which appears portrayed in panorama along the plot, and the love triangle, which I analyze in accordance with the ideas of Denis de Rougemont and René Girard. The third chapter deals specifically with the self-theoretical mechanisms in the novel Fanny Owen.
Keywords: autoteorização; narrador; biografia; romance de leitura; Fanny Owen; Agustina Bessa-Luís; self-theorization; narrator; biography; novel of reading; Fanny Owen; Agustina Bessa-Luís; CNPQ::LINGUISTICA, LETRAS E ARTES::LINGUISTICA